Perspectives in Curriculum Studies - Endeley, Margaret N.; Zama, Martha A. (Book collections on Project MUSE., 2021)
Perspectives in Curriculum Studies by Margaret Nalova Endeley and Martha Ashuntantang Zama is a comprehensive textbook for graduate students of Curriculum Studies and Instruction, and a guide for education practitioners wherein they articulate contemporary curriculum concepts, principles and applications in the field. With illustrations from informed African perspectives, the authors situate curriculum theory and practice in local contexts so that African scholars, educators, and others may be equipped with knowledge and skills to develop and maintain appropriate and relevant curricula for quality education.